An odyssey of process and engineering trends in forward osmosis. Issue 2 (14th December 2017) - Sreedhar, I.; Khaitan, Sneha; Gupta, Rajat; Reddy, Benjaram M.; Venugopal, A.
Abstract : Forward osmosis as a water treatment option has been extensively studied in recent decades owing to its energy efficiency and enhanced performance. Abstract : Forward osmosis as a water treatment option has been extensively studied in recent decades owing to its energy efficiency and enhanced performance. Even hybrid options of integrating forward osmosis with other separation technologies have been explored. In this article, forward osmosis has been comprehensively reviewed with reference to various process and engineering aspects viz., membranes, membrane fouling, contactors and their design, draw solutions, integration of forward osmosis with various other separation technologies and modeling, and simulation. Every aspect has been thoroughly reviewed and discussed in terms of development trends, in addition to presenting the future challenges and prospects.